Relationships Between Neurodegeneration and Vascular Damage in Diabetic Retinopathy - Rossino, Maria Grazia; Dal Monte, Massimo; Casini, Giovanni (Frontiers in Neuroscience, 2019)
Diabetic retinopathy (DR) is a common complication of diabetes and constitutes a major cause of vision impairment and blindness in the world. DR has long been described exclusively as a microvascular disease of the eye. However, in recent years, a growing interest has been focused on the contribution of neuroretinal degeneration to the pathogenesis of the disease, and there are observations suggesting that neuronal death in the early phases of DR may favor the development of microvascular abnormalities, followed by the full manifestation of the disease. However, the mediators that are involved in the crosslink between neurodegeneration and vascular changes have not yet been identified. According to our hypothesis, vascular endothelial growth factor (VEGF) could probably be the most important connecting link between the death of retinal neurons and the occurrence of microvascular lesions. Indeed, VEGF is known to play important neuroprotective actions; therefore, in the early phases of DR, it may be released in response to neuronal suffering, and it would act as a double-edged weapon inducing both neuroprotective and vasoactive effects. If this hypothesis is correct, then any retinal stress causing neuronal damage should be accompanied by VEGF upregulation and by vascular changes. Similarly, any compound with neuroprotective properties should also induce VEGF downregulation and amelioration of the vascular lesions. In this review, we searched for a correlation between neurodegeneration and vasculopathy in animal models of retinal diseases, examining the effects of different neuroprotective substances, ranging from nutraceuticals to antioxidants to neuropeptides and others and showing that reducing neuronal suffering also prevents overexpression of VEGF and vascular complications. Taken together, the reviewed evidence highlights the crucial role played by mediators such as VEGF in the relationship between retinal neuronal damage and vascular alterations and suggests that the use of neuroprotective substances could be an efficient strategy to prevent the onset or to retard the development of DR.